Analysis of chemotherapy symptoms reported via mobile application in patients with early breast cancer - Grašič Kuhar, Cvetka; Drmota, Eva; Gortnar, Tjaša; Kovač, Timotej; Kukar, Matjaž (Anali PAZU, 2022)
Cancer patients on chemotherapy treatment may have several symptoms. In the study Mobile application for patients with breast cancer treated with chemotherapy and targeted therapy patients reported symptoms by means of mobile application. Patient could report 50 symptoms. Patient having a specific symptom, defines a severity (mild, moderate or severe) and its duration. We performed analysis on 16 patients for the first cycle of chemotherapy. The most prevalent symptoms were fatigue (75%), dry mouth, headache, redness of the face (56%), myalgia, hoarsenes, heartburn, meteorism (31%), obstipation, diarrhoea (25%) and alopecia (44%). The majority of symptoms were mild or moderate and short lasting (less than 4 days). Reporting symptoms is of great help for the treating oncologist for better symptom treatment.
Keywords: cancer; chemotherapy; symptoms; mobile application